Extração, caracterização e aplicação do biopolímero da planta Pereskia aculeata miller como auxiliar coagulante/floculante no processo de tratamento de água - Lucca, Alexsandro (2017)
In the midst of the wide biodiversity of Brazilian flora, the ora-pro-nobis (Pereskia aculeata Miller) arouses special interest because of the high amount of mucilage in its leaves. Mucilage plants have been studied for some time in the flocculation / coagulation process in water treatments, with the intention of reducing or even succeeding the use of aluminum sulphate. Mucilage is a biopolymer with great gelforming, viscous solutions and stabilizing emulsion systems. The purpose of this study was to evaluate the yield of the mucilage in extraction processes, to characterize the clarified and clarified mucilage and to apply the clarified biopolymer of P. aculeata in the coagulation / flocculation process. For this, the leaves were oven dried to constant weight, the mucilage was extracted in aqueous solution by two different methodologies, evaluating the yield, characterization of the morphology by scanning electron microscopy (SEM) and X-ray diffractometry (XRD) (FT-IR), determination of potential zero charge pH and thermal behavior by thermogravimetric analysis (TG / DSC). For the evaluation of coagulation and flocculation, the biopolymer was evaluated in water of the Pato Branco River by tests in Jar Test evaluating the efficiency of the removal of turbidity, removal of humic and aromatic substances. The extraction of the mucilage was evaluated in the yield of the production, in which the extraction at 95 ºC (30 min) yielded a three times higher yield than the extraction at 60 ºC (6 hours). The morphological characterization showed an amorphous structure, spongy and with adhesion of smaller particles to the surface of larger particles, indicating a hygroscopic material that can be used as a coagulant, being similar to other mucilages studied, in aspects of functional groups and thermal behavior. P. aculeata was confirmed as an aid in the coagulation / flocculation process in relation to the parameters and ranges studied, being more effective in conjunction with aluminum sulphate. As it is an easy-to-grow, non-toxic plant with relatively low cost for the extraction of its biopolymer, it is a promising alternative in the treatment of water and effluents by reducing the use of aluminum sulphate in the flocculation / coagulation process.